PREDICTION OF HIGH-RISK NSSNPS ASSOCIATED WITH WISP3 GENE EXPRESSION: AN IN SILICO STUDY - M. S., SAUNDARYA; DINESH, SUSHA; SHARMA, SAMEER (International Journal of Applied Pharmaceutics, 2023)
Objective: The primary aim of this investigation is to comprehensively examine the detrimental effects of non-synonymous single nucleotide polymorphisms (nsSNPs) on the WISP3 gene. This objective will be accomplished through intricate evaluations encompassing protein stability prediction, amino acid conservation analysis, investigation of protein-protein interactions (PPI), scrutiny of post-translational modifications (PTM), and the utilization of bioinformatics tools to forecast the potential association between nsSNPs and various diseases. By implementing these sophisticated methodologies, we aim to unveil the intricate mechanisms by which harmful nsSNPs influence the functionality and pathological implications of the WISP3 gene. Methods: Retrieved rsIDs of SNPs from the dbSNP database and filtered using 5 in silico programs. Selected nsSNPs were subjected to further analysis i.e., protein stability and conservation analysis, solvent accessibility analysis, PPI and PTM analysis, prediction and evaluation of both native and mutant protein, and identification of cancer association and gene expression analysis. Results: The study found that seven (C122Y, C145Y, C52Y, C78R, C75G, N233K, and R245I) of the nsSNPs are potentially vulnerable due to their higher conservancy and ability to reduce protein stability. Two (D271N and Q56H) of the nsSNPs from the initial screening were found to be associated with colon adenocarcinoma. Conclusion: The study's findings could help researchers design experiments to validate the predictions and develop potential treatments for diseases associated with the WISP3 gene.